AN EMPIRICAL ANALYSIS OF THE FINANCING OF METALLURGICAL SMES OF VALLE DEL CAUCA: 2000 -2006 - Rivera Godoy, Jorge Alberto (Cuadernos de Administración, 2008)
Tlús research identifies the financial structure and the factors that explain the capital structure of vallecaucanas SMEs of the metallurgical sector in the period 2000 -2006. By collating the results with theoretical models and empirical evidence there is no proof that it meets any of them; this promotes to generate deeper research on each of the determinants of capital structure. Supported by the main theories about the capital structure and its field trials at the international and national scope, and is used as metodhology the economic-finance analysis, and an econometric model ofData Panel. The study found differences in the financial structure and the factors that explain the longterm debt ofthe small, medium and SME, despite the similarity of their activity and belonging to the same region. The small company gets in more debt and the medium company concentrates its short-term debt. The detenninants of capital structure are: short term debt, volatility ofthe operational utility, tax protection different from debt, growth opportunity, profitability, tangible assets, size and age ofthe frrm.